Constitutional Court (MK) Interpretation Of The Element of Urgency In The Formation Of A Government Regulation instead of Law ( PERPPU): Constitutional Court (MK) Interpretation Of The Element of Urgency In The Formation Of A Government Regulation instead of Law ( PERPPU) - Nurasikin, Nurasikin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The number of government regulations, instead of laws (Perppu), formed by the Government due to urgent circumstances, such as the formation of the Job Creation Perppu, has now become a law. Perppu as Emergency Legislation is based on the reasons of Innerenootstand (internal emergency) in urgent circumstances in terms of substance, and urgent in terms of time. This research uses a normative legal research type, with the approach used being the statute, conceptual, and case study approaches. Based on the results of the research, the legal requirements for the birth of a Perppu are: There is a situation, namely an urgent need to resolve legal problems quickly based on the LawLaw, the required LawLaw does not yet exist so that a legal vacuum occurs, or there is a law but it is inadequate and the legal vacuum cannot be overcome by make ConstitutionConstitution in a way procedure normal Because it will take quite a long time, while these urgent situations need certainty to be resolved. However, it becomes a legal problem when the Perppu was formed but did not comply with the elements for creating a Perppu. The Constitutional Court can carry out the testing. Will, but until the moment. This rule is clear about the Court Constitution, which is entitled to interpret the Law according to a rule or Law.